Investigating the subsidence pattern of southwest Tehran using interferometric SAR time series - Asghari Beirami, Behnam; Seif, Mohammadreza (Ecological Questions, 2025)
Due to drought and underground water extraction, many plains in Iran are experiencing subsidence. Among these areas, we can mention the southwestern part of Tehran, which has a large resident population and has suffered severe subsidence in the last two decades. In order to study subsidence, various ground and aerial methods are used, and the interferometric synthetic aperture radar (InSAR) system is one of those techniques that measures accurate values of ground surface displacement with high spatial resolution across a large study area. The small baseline subset (SBAS) method is a remote sensing-based technique to analyze the time series of radar interferometry. It is particularly important to examine subsidence patterns over different time frames in a geographical area and their relationship with climatic parameters, such as precipitation, in remote sensing. In this context, this research uses the SBAS method to obtain the average displacement velocity field of southwest Tehran for the period from 2014 to 2017. The maximum amount of subsidence in this area is 174 mm per year along the satellite’s line of sight and 227 mm per year in the vertical direction. The time series obtained from InSAR shows the uplift during certain periods. This uplift is attributed to rainfall exceeding 20 mm before the uplift events, particularly in the last six measurements, where heavy rain has resulted in an uplift of up to 50 mm.